2007
DOI: 10.1111/j.1462-2920.2007.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of the vanchrobactin siderophore system of Vibrio anguillarum by removal of a chromosomal insertion sequence originated in plasmid pJM1 encoding the anguibactin siderophore system

Abstract: SummaryA chromosomal gene cluster encoding vanchrobactin biosynthesis and transport genes was identified in the Vibrio anguillarum serotype O1 strain, 775(pJM1), harbouring the anguibactin biosynthetic genes in the pJM1 plasmid. In this strain only anguibactin is produced as the vanchrobactin chromosome cluster has a RS1 transposition insertion into vabF, one of the vanchrobactin biosynthesis genes. Removal of this RS1 generating 775(pJM1)Δtnp, still resulted in the detection of only anguibactin in specific bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 45 publications
0
78
0
Order By: Relevance
“…The majority of the genes were conserved throughout the strains; however, the anguibactin biosynthesis and transport genes were found only on the pJM1 plasmid in the 775 strain, although the RV22 strain had homologues of the fatABCD genes. These genes appeared not to be expressed (5,51). The tonB1 and tonB2-ttpC clusters were found in all of the V. anguillarum strains, but only the tonB1 system was identified in V. ordalii.…”
Section: Fig 3 Genomic Islands Of Strain 775 Predicted By Islandviementioning
confidence: 86%
See 1 more Smart Citation
“…The majority of the genes were conserved throughout the strains; however, the anguibactin biosynthesis and transport genes were found only on the pJM1 plasmid in the 775 strain, although the RV22 strain had homologues of the fatABCD genes. These genes appeared not to be expressed (5,51). The tonB1 and tonB2-ttpC clusters were found in all of the V. anguillarum strains, but only the tonB1 system was identified in V. ordalii.…”
Section: Fig 3 Genomic Islands Of Strain 775 Predicted By Islandviementioning
confidence: 86%
“…The fur gene is located on Chr1, which also harbors the heme determinants, although we have also identified a heme-related V. cholerae hutR homologue on Chr2 (42,48,49,70). Genes involved in ferric vanchrobactin and/or ferric enterobactin transport are located on Chr1, although vanchrobactin biosynthesis in 775 is abrogated by a mutation in vabF and there are no biosynthesis genes for enterobactin (51). It is of interest that potential ABC transporters FvtB-FvtE for vanchrobactin and enterobactin uptake are found on Chr2.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is supported by the negative results in all attempts to detect fatDCBA transcripts by RT-PCR (data not shown). Furthermore, Naka et al (28) detected FatA in the OM of strain RV22 only when it was transformed with a pJM1 plasmid. These findings not only demonstrate that the FatA-mediated anguibactin acquisition system is inappropriate for use in the Trojan horse strategy but also bring up interesting questions about the origin and evolution of the vanchrobactin and anguibactin systems in V. anguillarum.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the pJM1 plasmid, containing most genes necessary for anguibactin production and transport, has been associated with the lack of production of vanchrobactin. Naka et al (28) showed that vabF in the V. anguillarum 775 (a strain carrying pJM1) chromosome is disrupted by the insertion sequence (IS) RS1. In the present study we detected the presence of RS1, an insertion that abolishes vanchrobactin biosynthesis, in vabF in all strains that carry pJM1 or pJM1-like plasmids (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The FvtE protein is involved in the uptake of vanchrobactin, a chromosomally encoded siderophore found in many V. anguillarum strains (193,194). In strains harboring pJM1-type plasmids, genes of the vanchrobactin system, including the fvtE gene, are present on the chromosome, but this system is inactivated by an insertion in one of the vanchrobactin biosynthesis genes (195).…”
Section: Transportmentioning
confidence: 99%